Sams teach yourself JavaScript and Ajax video learning. (Sams teach yourself., 2009)
"The Sams Teach Yourself JavaScript and Ajax Video Learning course is organized into 24 lessons, each designed to be completed in 10 minutes or less"--Resource description page